Distancing and Rapproching: Local Communities and Monuments in the Aegean Sea — A Case Study from the Island of Naxos. (1st February 2013) - Lekakis, Stelios
<x xml:space="preserve">Abstract</x> This paper argues that the distancing of the Greek public from its archaeological heritage and the omnipresence of superficial, touristic narratives is an issue not efficiently addressed by the relevant dialectics of cultural heritage management. In order to understand the roots and dynamics of this phenomenon, its theoretical and practical manifestations are approached, mainly in the context of the communities of the Aegean. Within this context and drawing from the author's experience of working for the Greek non-profit organization of MONUMENTA on the island of Naxos, this paper examines the aims and methodologies of the programme 'Local Communities and Monuments'; a public outreach programme with objectives to examine the bonds between local communities and the cultural heritage that surrounds them and raise awareness.